Pengaruh Pemeriksaan Pajak Terhadap Penerimaan Pajak Pada Kantor Pelayanan Pajak Pratama Di Wilayah Makassar Utara - Muhammad Minsar (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) STIE Tri Dharma Nusantara, 2020)
This study aimed to analyze the effect of tax audit to tax revenues. Respondents in this study were employees of tax (tax authorities) on KPP Makassar Utara. The amount of tax officials that the research samples are 88 tax officials tax services and tax audits. The sampling method used in the study was convenience sampling, while data processing method used is simple regression analysis. The results showed that the tax assessment is positive but not significant effect on tax revenue.